Neuropilin1-dependent paracrine signaling of cancer cells mediated by miRNA exosomal cargo - Claudia Palazzo; Roberta Mastrantonio; Noemi Gioelli; Erika Testa; Francesco Recco; Donatella Lucchetti; Giulia Villari; Alessio D’Alessio; Alessandro Sgambato; Flavio Mignone; Guido Serini; Maria Teresa Viscomi; et al. (Cell Communication and Signaling)
Abstract Background Neuropilin-1 (NRP1) is a transmembrane protein involved in surface receptor complexes for a variety of extracellular signals. NRP1 expression in human cancers is associated with prominent angiogenesis and advanced progression stage. However, the molecular mechanisms underlying NRP1 activity in the tumor microenvironment remain unclear. Notably, diffusible forms of NRP1 in the extracellular space have been reported, but their functional role is poorly understood. Methods Extracellular vesicles (EV) were isolated from conditioned media of diverse cancer cells. The quality of exosome-enriched preparations was validated by the presence of specific markers in western blotting, as well as by light scattering and nanoparticle tracking analysis. Wound healing, transwell, and digital real-time migration assays were carried out to assess the activity of cancer cell-derived exosomes in the regulation of endothelial cells. RNA interference was applied to obtain NRP1 knock-down, and cDNA transfer to achieve its overexpression, in exosome-releasing cells. The micro-RNA profile carried by exosomes was investigated by Next Generation Sequencing. miRNA-Scope in situ hybridization was used to assess the transfer of miRNA exosome cargo to target cells, and immunofluorescence analysis revealed expression regulation of targeted proteins. miRNA activity was blocked by the use of specific antago-miRs. Results In this study, we show that diverse human cancer cells release NRP1 embedded in exosome-like small extracellular vesicles, which mediate a previously unknown NRP1-dependent paracrine signaling mechanism regulating endothelial cell migration. By transcriptomic analysis of the cargo of NRP1-loaded exosomes, we found a significant enrichment of miR-210-3p, known to promote tumor angiogenesis. Gene knock-down and overexpression experiments demonstrated that the loading of miR-210-3p into exosomes is dependent on NRP1. Data furthermore indicate that the exosomes released through this NRP1-driven mechanism effectively transfer miR-210-3p to human endothelial cells, causing paracrine downregulation of the regulatory cue ephrin-A3 and promotion of cell migration. The mechanistic involvement of miR-210-3p in this pathway was confirmed by applying a specific antago-miR. Conclusions In sum, we unveiled a previously unknown NRP1-dependent paracrine signaling mechanism, mediated by the loading of pro-angiogenic miR-210-3p in exosomes released by cancer cells, which underscores the relevance of NRP1 in controlling the tumor microenvironment.